Re-painting the mainstream archive black: a close reading of the iconography on instagram by Mary Sibande, Zanele Muholi, Thenjiwe Niki Nkosi and Lady Skollie - Gcilitshane, Lerato (My University, 2021)
This research project explores the work of four Black South African women artists, Mary Sibande, Zanele Muholi, Thenjiwe Niki Nkosi and Lady Skollie, who have disrupted political, social and narrative structures within the traditional art and mainstream media industries as well as the larger society. Their artworks are read as feminist public artworks that have expanded and altered public spaces as well as posed a challenge to exclusionary and racially biased constructs of mainstream media and culture. This is an interdisciplinary study that straddles the lines of visual art and media studies. In conducting this research, direction is focused on the platform of Instagram as an interface for visual imagery and images. It is argued that the form that these artists and their visual works have taken has disrupted space and viewing on Instagram. This study is significant because Black women's bodies have been historically subjected to objectification, exclusion and silencing. It is therefore important to build a body of scholarly work that will become part of the greater decolonial project aimed at troubling pre-set constructs by reforming and taking control of visual images of Black women and their narratives. Furthermore, this research study, as written by a Black scholar is important in continuing to build the written archive by young Black women and building their own narrated experiences within mainstream public spaces. The array of literature in this study explores the extent to which Black women have been represented in visual culture. As the artist’s works are read as feminist, due to their parallel nature of placing women at the forefront, Black feminisms were used to frame this study. This was also supported by theories of performativity and an exploration of alternative public art. The research was conducted through a Cyber Ethnography and Thematic Content Analysis and provided an outcome that visual works have taken on a new form on Instagram and extended art exchange and engagement practices. As a result of this relationship, visual artworks have altered this digital space and gained a life and identity of their own in addition to their presence in art galleries. Essentially, Instagram plays a large role and influence in reforming the Black visual mainstream archive.
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, 2021